Tolerance of salinity bell pepper cultivars (Capsicum annuum L.) in germination and initial growth (Research, Society and Development, 2021)
The use of cultivars tolerant to salinity is one of the strategies for food production in regions affected by soil salinization. The objective of this study was to evaluate the tolerance of pepper cultivars to saline stress during the process of seed germination and seedling development. The experiment was conducted in the laboratory, adopting a completely randomized design, in a factorial scheme, with four replicates. The first factor consisted of two pepper cultivars (Casca Dura Ikeda and Amarelo SF 134); and the second five levels of water salinity (0.0; 3.0; 6.0; 9.0 and 12.0 dS m-1). Germination, first germination count, germination speed index, average germination time, seedling length, root and shoot dry matter and salinity tolerance index were evaluated. In general, the salinity of the water promoted deleterious effects on the germination and seedling growth of the two cultivars from the EC 6.0 dS m-1. The cultivar ‘Amarelo SF 134’ indicates greater tolerance to salt stress in the germination process, while ‘Casca Dura Ikeda’, in the initial seedling growth phase.